Yousefi, S., Rahimian, H., Nabavi, S.M.B. & Glasby, C.J. (2011) Nereididae (Annelida: Polychaeta) from intertidal habitats in the Gulf of Oman, Iran. Zootaxa, 3013, 48–64. - Yousefi, S; Rahimian, H.; Nabavi, S. M.b.; Glasby, C. J. (Zootaxa, 2013)
It has come to our attention that in the work referenced above we unintentionally referred to the body of water separating the Iranian Plateau from the Arabian Peninsula as the ‘Arabian Gulf ‘(Abstract, line 9). The words ‘Arabian Gulf’ should be replaced with the words ‘Persian Gulf’, which is the name for this water mass recognised by the International Hydrographic Organization (1953) and endorsed by the UN Group of Experts on Geographical Names (2006). International Hydrographic Organization (1953). Limits of Oceans and Seas (special publication No 23). 3rd edition. [pdf accessed at http://www.iho.int/iho_pubs/IHO_Download.htm 22 Jan 2013] Report of the United Nations Group of Experts on Geographical Names on the work of its twenty-third session. Document E/2006/57, Economic and Social Council, United Nations. New York, 2006 [pdf accessed at http://unstats.un.org/unsd/geoinfo/UNGEGN/docs/23-gegn/wp/gegn23wp61.pdf 22 Jan 2013]